2010
DOI: 10.1017/s1461145710000234
|View full text |Cite
|
Sign up to set email alerts
|

Phencyclidine withdrawal disrupts episodic-like memory in rats: reversal by donepezil but not clozapine

Abstract: Episodic memory is the capacity to recall an event in time and place (What? Where? When?). Impaired episodic memory is a debilitating cognitive symptom in schizophrenia but is poorly controlled by currently available antipsychotic drugs. Consistent with glutamatergic abnormality in schizophrenia, the NDMA receptor antagonist, phencyclidine (PCP), induces persistent 'schizophrenia-like' symptoms including memory deficits in humans and rodents and is widely used as an animal model of the disorder. However, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…In previous studies, donepezil has been found to reverse sub-chronic PCP-induced (McLean et al, 2011a;Kunitachi et al, 2009;Le Cozannet et al, 2010) and scopolamineinduced deficits (Lenz et al, 2012) in rodents. In support of our data in a model of delayinduced deficits, donepezil (0.1-3 mg/kg) alleviates object recognition deficits following a 4 hour inter-trial interval (Kendall et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies, donepezil has been found to reverse sub-chronic PCP-induced (McLean et al, 2011a;Kunitachi et al, 2009;Le Cozannet et al, 2010) and scopolamineinduced deficits (Lenz et al, 2012) in rodents. In support of our data in a model of delayinduced deficits, donepezil (0.1-3 mg/kg) alleviates object recognition deficits following a 4 hour inter-trial interval (Kendall et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, many of the PCP‐induced cognitive deficits appear to be reversed by several atypical antipsychotics. However, acute clozapine failed to reverse a subchronic PCP‐induced impairment in episodic memory (Le Cozannet et al ., 2010), and only sertindole, but not risperidone, restored performance in the extra‐dimensional shift of the attentional set‐shifting task (Goetghebeur and Dias, 2009). Few studies have evaluated the effect of repeated or chronic antipsychotic drug treatment on cognitive impairment in PCP models.…”
Section: Pharmacological Modelsmentioning
confidence: 99%
“…The deficit was reversed by acute treatments with atypical antipsychotic compounds ziprasidone, olanzapine, and clozapine. PCP withdrawal impaired performance in object-placecontext task in rats, which was reversed by donepezil but not by clozapine (Le Cozannet et al, 2010). Subchronic PCP treatment induced a persistent deficit in novel object recognition that was attenuated by lurasidone (a potent 5-HT 1A partial agonist, 5-HT 2A antagonist), tandospirone (weak D 2 antagonist), and F15599 (selective postsynaptic 5-HT 1A agonist), and interaction studies with these various ligands showed that 5-HT 1A agonism was adequate to attenuate the PCP-induced effects (Horiguchi and Meltzer, 2012).…”
Section: F N-methyl-d-aspartate Receptor Antagonistsmentioning
confidence: 91%